Dynamic Liquid Gating Artificially Spinning System for Self-Evolving Topographies and Microstructures - Gao, Wei (Langmuir : the ACS journal of surfaces and colloids, 2021)
Developments in spinning systems have triggered revolutions ranging from bioengineering tissue scaffolds to emerging smart wearable fabrics, but the structures of the spinning fibers are usually limited by intrinsic channel configurations and the "dead" nozzle's geometry. In contrast, natural living systems, such as a spider spinning apparatus, use a "live" gate to coordinate microstructures via shearing and expanding at both axial and radial directions. Herein, for the first time, we introduce a dynamic liquid gating effect in artificial systems to mimic the spinning in biological organisms. Theoretical modeling and experimental regime diagram demonstrate that the topographies and microstructures of the fibers self-evolve after passing through the liquid gate and they could be tuned over a wide range, which successfully exceeds the limits of current "dead" spinning channels. In particular, fibers with a periodic spindle-knot structure self-evolve from a water gate and show fast directional water collecting and intelligent sensing ability. The liquid gating design not only sheds new light on fiber structure control in multiple spatiotemporal dimensions but also contributes to the development of high-performance fibers with sophisticated functions